2011
DOI: 10.1093/europace/eur138
|View full text |Cite
|
Sign up to set email alerts
|

Persistent iatrogenic atrial septal defect after pulmonary vein isolation by cryoballoon: an under-recognized complication

Abstract: Persistent IASD is a common complication after PVI by cryoballoon catheter. Only left-to-right, but not right-to-left, interatrial shunting occurred as a result of the IASD. There was no clinical occurrence of paradoxical embolism. Patients should be screened for this complication after cryoballoon procedures and regular reassessment with echocardiographic or other techniques should be performed for monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…2 The next-day size of the iASD correlated with its persistence at 12 months. Persistent iASD has been reported in up to 38% of patients at 6 months and in 15% to 20% of patients at 12 months among those who had a transseptal puncture performed for access to the left atrium during cryoablation 3,4 ; the clinical significance of this remains unknown. 5 The mean size of the iASD ranged from 4.6 to 5.7 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The next-day size of the iASD correlated with its persistence at 12 months. Persistent iASD has been reported in up to 38% of patients at 6 months and in 15% to 20% of patients at 12 months among those who had a transseptal puncture performed for access to the left atrium during cryoablation 3,4 ; the clinical significance of this remains unknown. 5 The mean size of the iASD ranged from 4.6 to 5.7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Only a left-to-right shunt was seen, and no embolism was reported. 3,4 Recent reports have shown that the risk factors for extensive damage to the fossa Heart Rhythm, Vol 0, No 0, Month 2015 ovalis region, resulting in persistent iASD after cryoablation, relate to the large sheath size along with intense maneuvering of the transseptal sheath to reach and isolate the pulmonary veins successfully. 5 No functional sequelae of these iASDs have ever been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although shunting through iASD is documented universally, follow-up or closure is not routinely performed. The shunt is predominantly left-to-right in an otherwise structurally normal heart while right-to-left shunting can be observed in patients with underlying right atrial pressure elevation [12].…”
Section: Shunting Through the Defectmentioning
confidence: 99%
“…Only a portion of patients has residual iASD, and the defect tends to close spontaneously overtime [12]. Chan et al observed the incidence of iASD after cryoballoon ablation significantly reduced from 38% at 6 months to 31% at 9 months [12].…”
Section: Dealing With the Defectmentioning
confidence: 99%
See 1 more Smart Citation